Social media choices and uses: comparing Turkish and American young-adults' social media activism - Burke, Barbara Ruth; Sen, Ayse Fulya (Palgrave Macmillan Ltd, 2018)
Advocates of new media-especially social networks, blogs, and photo/content sharing sites-argue that these tools create transformative impacts on society. Recently, around the world younger activists in popular democracy movements, uprisings, and protests, feeling disengaged by traditional forms of political discourse, have debated their positions on new media, and have used digital media to communicate, organize, and coordinate protest activities. While some media scholars suggest this is an indication that young people are active in creating a public sphere constructed by social media, there is still little real-world evidence that the technological potentials are widely realized. To address this gap, this comparative case study aims to reveal how some ordinary young people are using social media in response to political issues, investigating: if social media create a new kind of dynamic arena for their public activism; which factors may stimulate the young to activism; and whether their motivation is powerful enough to resist the status quo. Describing and analyzing qualitative interview data from a study of Turkish students and a parallel collection of data from US students, we construct an explanation of their communicated understandings of their differences and similarities in opportunities for political actions. Our findings indicate: there are many similar technical capacities; some similar topics are seen as political; and there are different understandings of what is and is not for public discussion among their personal collections of contacts and friends, with varying levels of real-world connections. This analysis is important in terms of understanding the ways uses of media technologies may be affected by different cultures, political and social conceptualizations and online communication patterns.
Keywords: Action Repertoires; Exposure; Internet; News